2015
DOI: 10.1002/minf.201400147
|View full text |Cite
|
Sign up to set email alerts
|

The Permeability of an Artificial Membrane for Wide Range of pH in Human Gastrointestinal Tract: Experimental Measurements and Quantitative StructureActivity Relationship

Abstract: In silico models for membrane permeability have been based on values measured for single pH. Depending on the diet (fasted/fed state) and part of human intestine the range of pH varies approximately from 2.4 to 8.0. This motivated to study and model the membrane permeability of chemicals considering the whole range of pH in the human intestine. For this, effective membrane permeability values were measured for 65 drugs and drug-like compounds using PAMPA method at four pHs (3, 5, 7.4, 9) over 48 h, introducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…However, PAMPA permeability is sensitive to the assay conditions (vide supra). To warrant data consistency and to minimize the variations in assay conditions among different data sources [34,38,39,40,41,42,51,55,75,77,78,79,80], only those molecules assayed by Oja and Maran [39,41,42] were selected in this study since they generated the largest quantity of data. If there were two or more available efflux ratio data for a given compound and in close range, the average values were then taken in order to warrant better consistency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PAMPA permeability is sensitive to the assay conditions (vide supra). To warrant data consistency and to minimize the variations in assay conditions among different data sources [34,38,39,40,41,42,51,55,75,77,78,79,80], only those molecules assayed by Oja and Maran [39,41,42] were selected in this study since they generated the largest quantity of data. If there were two or more available efflux ratio data for a given compound and in close range, the average values were then taken in order to warrant better consistency.…”
Section: Methodsmentioning
confidence: 99%
“…As such, in silico approaches play an increasing role in ADME/Tox profiling [27]. In fact, numerous qualitative structure–activity relationship (QSAR) models have been developed to predict PAMPA permeability [7,23,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…1315 A number of physical models have been proposed to predict passive membrane permeation, in an attempt to simulate the underlying physical permeation process. 16 The majority of the physical models exhibited poor predictability based on the small datasets, partly due to complexity of the permeation process and lack of reliable parameters to formulate the equations associated with the process.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of studies reported models for PAMPA permeability in literature. 3135 Most studies either use a different kind of assay to measure PAMPA permeability or use small datasets comprising a few hundred compounds. Searching by keyword “PAMPA” resulted in a total of 935 assay records and 1015 measurements on ChEMBL.…”
Section: Resultsmentioning
confidence: 99%